Body roundness index and cognitive function in older adults: a nationwide perspective - Zhang, Feng; Ning, Zhongxing; Wang, Can (Frontiers in Aging Neuroscience, 2024)
BackgroundObesity negatively impacts cognitive function. However, the correlation between the body roundness index (BRI) and cognitive performance remains inadequately explored.MethodsThis study used data from the National Health and Nutrition Examination Survey (NHANES) collected from 2011 to 2014 to examine the correlation between BRI and cognitive function in individuals aged 65 and older. Models of multiple linear regression were used to investigate the relationship between BRI and cognitive performance. Additionally, smoothed curve fittings explored potential non-linear associations. Interaction tests and subgroup analyses were also performed.ResultsOne thousand eight hundred seventy participants were taken into account, revealing an important negative relationship between BRI levels and cognitive performance. In the fully adjusted model, elevated BRI was substantially correlated with lower Digit Symbol Substitution Test (DSST) scores (β = −0.34, 95% CI = −0.64 to −0.05, p = 0.023), indicating that the higher BRI values are linked to worse cognitive performance. Sex differences were observed, with males showing a stronger negative association (p for interaction = 0.040).ConclusionElevated BRI is related to worse cognitive function in the elderly population.